Adapting the Bebras Challenge into an Educational Game for Learning Computational Thinking and Assessing Its Usability - Sukirman, Sukirman; Yuliana, Irma; Ramadhan, Fakhri Aulia Wildan (UNDIKMA, 2026)
Computational thinking (CT) has become an essential component of secondary education, with several countries, including Indonesia, integrating CT tasks, such as those from the Bebras Challenge, into the national informatics curriculum. However, these tasks are often presented in static and text-based formats, limiting their potential to engage learners in interactive and meaningful ways. This study aimed to develop and evaluate the usability of an educational game adapted from a Bebras Challenge problem,